2014
DOI: 10.1007/s10555-014-9521-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of MTA1 in head and neck cancers

Abstract: Head and neck cancers usually originate in the squamous cells that line the inner mucosal surfaces of the oral and the neck region. These cancers follow multifocal steps for progression that include risk of developing metastasis. Although therapeutics has advanced in the past decades, head and neck cancers continue to cause much morbidity and mortality. Even with the promising effect of targeted therapies, there is a need for a better evaluation of patients with head and neck cancers. Metastasis-associated tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
(67 reference statements)
1
14
0
Order By: Relevance
“…[65][66][67] Previous studies revealed that MTA1 is one of the most upregulated proteins in human cancer, and it is associated with cancer progression, aggressive phenotypes, and poor prognosis in patients with cancer. 26,67 In the present study, both DcR3 and MTA1 were overexpressed in OSCC patients (Figures 2 and 5), and MTA1 was positive correlated with DcR3 expression in the clinical data ( Figure 5A). Interestingly, TPL repressed both DcR3 and MTA1 expression in vitro, in vivo, and in the PDTX model of OSCC (Figures 3-5).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…[65][66][67] Previous studies revealed that MTA1 is one of the most upregulated proteins in human cancer, and it is associated with cancer progression, aggressive phenotypes, and poor prognosis in patients with cancer. 26,67 In the present study, both DcR3 and MTA1 were overexpressed in OSCC patients (Figures 2 and 5), and MTA1 was positive correlated with DcR3 expression in the clinical data ( Figure 5A). Interestingly, TPL repressed both DcR3 and MTA1 expression in vitro, in vivo, and in the PDTX model of OSCC (Figures 3-5).…”
Section: Discussionsupporting
confidence: 59%
“…Overexpression of MTA1 is associated with the progression of various cancer types, including those of the head and neck. 25,26 These results suggest that the correlation between DcR3 and MTA1 might contribute to cancer progression in patients with OSCC.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Metastasis‐associated protein 1 (MTA1), with MTA2 and MTA3, belongs to a family of chromatin modifier . MTA1 plays a major part in the nucleosome remodeling and histone deacetylation (NuRD) complex, which has the capability of transcriptional regulation and chromatin remodeling . Collective evidence has demonstrated the role of MTA1 in tumor cell metastasis and progression.…”
Section: Introductionmentioning
confidence: 99%